Through stone and sea : a novel of the Noble dead - Hendee, Barb (Hendee, Barb. Noble dead saga., 2010)
Young scholar Wynn Hygeorht remains determined to recover ancient texts she brought back from the castle in the Farlands. To do so, she will have to journey to the mountain stronghold of the dwarves with two uncertain allies as guides. But there she will find more puzzles and questions buried in secrets old and new-along with an enemy she thought destroyed...